ChemInform Abstract: An Unexpected One Step Domino Conversion of TMS‐Alkynes to Protected Ketones in 4‐Chromenone System. Issue 1 (7th January 2014) - Bhattacharya, Prabuddha; Basak, Amit
Abstract An unexpected one‐pot conversion of Tms‐substituted 3‐ethynyl‐4‐chromenones to ketals of type (III) is reported.